Entrepreneurship and Agribusiness Elements in the MYPEs (GnosisWisdom, 2025)
Entrepreneurship and agribusiness elements in MSEs represent a field of great importance for economic and social development, especially in the agricultural sector; however, many microenterprises face challenges related to informality, low competitiveness and limited knowledge about the key elements of agribusiness, leading to a high rate of closures in their first years of operation. The aim was to systematize information on the relationship between entrepreneurship and agribusiness in MSEs, highlighting the elements that influence their sustainability and success, such as technological innovation, training and access to markets. We reviewed and selected scientific articles in databases such as SciELO and Scopus that met the inclusion and exclusion criteria, analyzing such research from a heuristic and hermeneutic perspective of the state of the art. Among the results, it is highlighted that the strengthening of entrepreneurial capacities and the integration of technology in productive processes are determining factors for the success of agribusinesses in microenterprises. It is concluded that there is a significant relationship between entrepreneurship and agribusiness development, and that MSEs that manage to integrate these elements have greater possibilities of growing and maintaining themselves in the market, improving their competitiveness.
Keywords: Entrepreneurship; agribusiness; MYPEs